Proton pump inhibitors to control phosphorus levels in hemodialysis patients - Amineh Hojati (Caspian Journal of Internal Medicine, 2025)
Researchers and healthcare providers can advance the field of phosphorus control, ultimately improving patient outcomes and enhancing the overall quality of care for ESKD patients.